Substantial heritable variation for susceptibility to Dothistroma septosporum within populations of native British Scots pine (Pinus sylvestris). (4th April 2016) - Perry, A.; Wachowiak, W.; Brown, A. V.; Ennos, R. A.; Cottrell, J. E.; Cavers, S.
Abstract : The threat from pests and pathogens to native and commercially planted forest trees is unprecedented and expected to increase under climate change. The degree to which forests respond to threats from pathogens depends on their adaptive capacity, which is determined largely by genetically controlled variation in susceptibility of the individual trees within them and the heritability and evolvability of this trait. The most significant current threat to the economically and ecologically important species Scots pine ( Pinus sylvestris ) is dothistroma needle blight (DNB), caused by the foliar pathogen Dothistroma septosporum . A progeny‐population trial of 4‐year‐old Scots pine trees, comprising six populations from native Caledonian pinewoods each with three to five families in seven blocks, was artificially inoculated using a single isolate of D. septosporum . Susceptibility to D. septosporum, assessed as the percentage of non‐green needles, was measured regularly over a period of 61 days following inoculation, during which plants were maintained in conditions ideal for DNB development (warm; high humidity; high leaf wetness). There were significant differences in susceptibility to D. septosporum among families indicating that variation in this trait is heritable, with high estimates of narrow‐sense heritability (0.38–0.75) and evolvability (genetic coefficient of variation, 23.47). It is concluded that native Scots pine populations contain sufficient genetic diversity to evolve lower susceptibility to D. septosporum through natural selection in response to increased prevalence of this pathogen.